You are on page 1of 1

ModuliSpaces@HKG

Using IBP, we obtain
Z ∞
0

Z ∞
sinn x
−1
dx
=
sinn xd(x−n+1 )
xn
n−1 0
Z ∞
1
(sinn x)0
=
dx
n−1 0
xn−1
= ...
Z ∞
1
(sinn x)(n−1)
=
dx.
(n − 1)! 0
x

Note that we have

n−1 


2
X

n−1
1
n


2 −k
(−1)
sin((n − 2k)x)


n−1
k
2
n
k=0
sin x =
n 
 


2
X

n
1
n
1
n


2 −k
(−1)
+
cos((n − 2k)x)

 2n n
n−1
2
k
2

if n is odd
if n is even

k=0

Hence
n

(n−1)

(sin x)

=

[ n−1
2 ]

1

X

2n−1

(−1)k

k=0 


n
(n − 2k)n−1 sin((n − 2k)x).
k

Then we get
Z
0

n−1 


[ 2 ]
Z ∞
X
sinn x
1
sin((n − 2k)x)
k n
n−1
dx
=
(−1)
(n

2k)
dx
xn
2n−1 (n − 1)!
k
x
0
k=0
n−1 


[ 2 ]
X
1
n
π
= n−1
(−1)k
(n − 2k)n−1 (sgn(n − 2k) )
2
(n − 1)!
k
2
k=0

[ n−1
2 ] 


X
π
k n
= n
(−1)
(n − 2k)n−1 ,
2 (n − 1)!
k
k=0

Z
since sgn(n − 2k) = 1 and
transform.

0

sin((n − 2k)x)
π
dx = sgn(n − 2k) by Laplace
x
2

1